Implementing STEAM education in the independent curriculum: Enhancing 21st century skills - Ismiati, Nur (Tadibia Islamika: Journal of Holistic Islamic Education, 2024)
STEAM education integrates the elements of science, technology, engineering, art, and mathematics into a cohesive learning model. This interdisciplinary approach not only enhances students' academic skills but also fosters critical thinking, creativity, and innovation. In this context, STEAM education emerges as a promising alternative to traditional teaching methods, aligning well with the goals of the independent curriculum. The primary objective of this study is to explore and elucidate the implementation of STEAM education within the framework of the independent curriculum. Researchers adopted a descriptive qualitative research methodology, focusing on comprehensive literature reviews to gather relevant data. This method allowed for a detailed examination of existing studies and practices related to STEAM education. The study's findings reveal that integrating STEAM into the curriculum offers a multifaceted approach to teaching. It encourages students to engage in project-based learning, which promotes hands-on experience and practical application of theoretical knowledge. Through these projects, students are not only exposed to technological tools and mathematical concepts but also learn to observe and analyze real-world phenomena critically. Furthermore, STEAM education's emphasis on art alongside traditional STEM subjects nurtures a holistic development, fostering both analytical and creative skills. This blend of skills is crucial for preparing students to navigate and succeed in an increasingly complex and dynamic world. In conclusion, the implementation of STEAM-based education within the independent curriculum can significantly contribute to developing 21st-century skills. By fostering critical thinking, creativity, and innovative problem-solving abilities, STEAM education aligns with and supports the overarching goals of the independent curriculum, making it a valuable educational strategy for modern learning environments.